EVALUASI KINERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN ESSANG SELATAN KABUPATEN KEPULAUAN TALAUD - LARENGGAM, SRIA; OGOTAN, MARTHA; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2018)
abstract:The quality of human resources of the State Civil Apparatus in government agencies is one of the factors to improve the productivity of an organization’s performance or organization, therefore, it is necessary human resources who have high competence professionalism as this will be able to support the improvement f civil servant performance. Professionalism in accordance with the competence,work rules and rank levels assigned to the position and other objective conditions without distinction of sex, race, race, race or class. The implementation of stff coaching can be a process of change from untrained employees transformed into employees-employees can now be developed to assume new responsibilities. To measure the success or failure of the program implemented then required the assessment and evaluation systematically. To measure performance, multiple performance measures can be used. Which cover; quantity of work, quality of work, knowledge of work, creativity, cooperation, work inevitability, initiative and personal qualities. This research uses data collection technique that is descriptive qualitative research through data collection technique that is data reduction, data presentation, and conclusion. Performance is a manifestation of the ability and success of an organization in carrying out its duties and functions. In this research, the performance of State Civil Appratus in South Essang District office of Talaud Islands Regency is seen from the performance indicators, namely: job quanlity, job quality, job knowledge, creativity, cooperation, firmness in work, initiative personal quality. Keywords: performance Evaluation of State Civil Apparatus